Legal and Humanitarian Implications on The Highway (Case Study of Ambulance Ticketed ETLE) - Indah Sekar Arum; Hanin Alya' Labibah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study aims to examine the legal and humanitarian implications of the Electronic Traffic Law Enforcement (ETLE) system when applied to emergency vehicles such as ambulances that violate traffic regulations during life-saving missions. The research employed a normative legal method supported by statutory and conceptual approaches, complemented by limited empirical observations. The method analyzed primary legal materials, including traffic legislation and constitutional provisions, and secondary materials such as journal articles on digital law enforcement and algorithmic decision-making. The novelty of this research lies in its identification of structural weaknesses in Indonesia’s automated ticketing system, which fails to differentiate ordinary traffic violations from emergency-based exceptions, resulting in potential conflicts with the constitutional right to life. The findings demonstrate that ETLE operates rigidly because it relies solely on visual camera detection without integration with emergency vehicle databases. This creates legal inconsistency, particularly with Articles 134–135 of the Traffic Law and Article 28A of the Constitution. The research also reveals a technological gap due to the absence of adaptive algorithms, real-time vehicle identification, and human-override mechanisms. Based on these findings, the study concludes that ETLE requires regulatory refinement, technological upgrading, and inter-institutional integration to ensure that automated enforcement remains aligned with principles of justice and humanitarian protection. The study recommends developing an integrated whitelist system, real-time data synchronization with emergency services, and the inclusion of contextual AI-based analysis to prevent the penalization of life-saving actions.